Unilateral contact buckling behaviour of orthotropic plates subjected to combined in-plane shear and bending. (1st October 2018) - Dong, Jianghui; Ma, Xing; Zhuge, Yan; Mills, Julie E.
Abstract: This paper addresses the buckling behaviour of a long thin orthotropic plate on a tensionless rigid foundation under combined in-plane shear and bending, where the sheet can only buckle away from the foundation due to the tensionless foundation support. Two boundary conditions at the longitudinal edges ( y  = 0 and b ) are investigated, i.e. clamped and simply supported. The energy method is used to derive the explicit expression for the lateral buckling mode function. The buckling response is then obtained by solving the governing differential equation after substituting the lateral buckling mode function. Based on the analytical solutions developed in the paper, fitted formulae are given for buckling coefficients and the interaction curve. Finally, a numerical example of a corrugated sheet is given to verify the presented model through comparing the results with finite element (FE) analysis.